PS02.243: THE EFFECT OF PREHABILITATION ON SARCOPENIA DEVELOPMENT DURING NEOADJUVANT CHEMOTHERAPY FOR OESOPHAGOGASTRIC CANCER: A RANDOMISED CONTROLLED TRIAL. (14th September 2018) - Allen, Sophie; White, Daniel; Rockall, Timothy; Preston, Shaun; Sultan, Javed
Abstract: Background: Neoadjuvant chemotherapy (NAC) and surgery improves 5-year survival in patients with oesophagogastric (OG) cancer. NAC induces loss of skeletal muscle mass and function, leading to the development of sarcopenia (defined as > 5% skeletal muscle (SM) loss in patients with a BMI of > 20kg/m 2 ). This is a poor prognostic indicator of outcome. We assess whether a prehabilitation programme (during NAC) results in a reduced rate of SM loss compared with 'standard care'. Methods: A single-centre, randomised controlled trial was conducted in patients undergoing NAC for OG cancer. Patients were assigned to a 15-week prehabilitation programme comprising twice weekly supervised aerobic and resistance training and a thrice weekly home exercise plan (Prehab), or standard care (Control). Patients underwent CT imaging at baseline (week 0) and following NAC (week 10). Analysis was performed using Tomovision SliceOmatic software, with a single slice at the third lumbar vertebra. Height provided the skeletal muscle index (SMI, cm 2 /m 2 ). Hand grip strength (HGS) using an analogue dynamometer at weeks 0 and 10 supplied functional outcome. Results: Since December 2016, 46 patients have been recruited, with a 15% drop-out rate (7/46). All patients received NAC. To date, complete dataset is available for 29 subjects (Prehab n = 16; Control n = 13). Groups were matched for baseline demographics, SMI and HGS ( P  = ns): Mean SMI 53.71 ± 10.15cm 2 /m 2 and HGS 46 ± 11.13kg at baseline. There was a weak correlation between baseline HGS and SMI (0.58). No difference was observed in the rate of sarcopenia development during NAC (Prehab 68.75% (11/16) vs. Control 69.23% (9/13); P  = 0.98), however there was a non-significant trend towards a smaller amount of skeletal muscle loss in Prehab subjects compared with Controls (-3.02 ± 3.22 cm 2 /m 2 vs. -5.28 ± 3.00cm 2 /m 2 ; P  = 0.38). Similarly, NAC induced a trend towards lesser decline in mean HGS in the Prehab group versus Controls (-1.07 ± 1.28 kg vs. -2.08 ± 3.84kg; P  = 0.25). A greater mean visceral fat loss was seen in the Prehab subjects compared with Controls (-16.04 vs -7.95; P  = 0.02). Conclusion: Interim analysis demonstrates a trend towards preservation of muscle mass and HGS, and significantly more visceral fat loss in patients receiving prehabilitation during NAC. Trial completion is warranted. The full dataset will be available by June 2018. Disclosure: All authors have declared no conflicts of interest.